Report on the socioeconomic, humanitarian and human rights situation in the PalmaAfungi-Mocímboa area (Cabo Delgado) - Rufin, Jean-Christophe; Glowacki, Ingrid (Total Energies, 2023)
Patrick Pouyanné, Chairman and CEO of TotalEnergies, entrusted Jean-Christophe Rufin in December 2022, on behalf of the partners of the Mozambique LNG project, with an independent mission to assess the humanitarian situation in the province of Cabo Delgado where the project is located. Jean-Christophe Rufin, a recognized expert in the field humanitarian action and human rights, has carried out several investigation field trips in Mozambique. TotalEnergies publishes his report as well as the action plan decided by Mozambique LNG partners based on the recommendations of the report. The report recalls that the conflict in the province of Cabo Delgado has origins pre-dating the gas development projects and finds its roots in multiple factors not related to Mozambique LNG. It assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. The report assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. It notes an improved humanitarian situation in the north of Cabo Delgado, in particular with the return of the populations displaced by the conflict to the town of Palma and to a lesser degree to the town of Mocímboa da Praia. The report highlights the execution quality of the actions undertaken by Mozambique LNG and their positive impact on the living conditions of local population. However it recommends the establishment of a dedicated structure with increased resources to further expand these programs and to integrate them into an ambitious and sustainable strategy of local development covering the whole province, and not only guided by the security of the project site. Regarding the populations affected by the development of the Afungi industrial site, Jean-Christophe Rufin recommends several avenues of improvements to finalize in the best conditions the implementation of the resettlement plan and ensure the compensation of affected persons in accordance with the best practices. These improvements relate in particular to the update of the inventories of the affected persons’ assets, the payment timeline of compensations, the provision of agricultural land and the access to fishing areas.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; conflict / conflito; displaced communities / comunidades deslocadas; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; infrastructure - energy / infrastrutura - energia; natural resources - gas / recursos naturais - gás; private sector / setor privado; security / segurança; social action / ação social

Os espaços de participação e de exercício da cidadania, na voz de líderes associativos da província de Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
O texto descreve os obstáculos históricos ao desenvolvimento de organizações da sociedade civil (OSC) em Moçambique, que conheceram um cenário mais acolhedor na Constituição de 1990. Mecanismos de apoio à sociedade civil capacitaram líderes locais, tornando-os melhor conhecedores de dispositivos legais, capazes de reunir evidências e de exercer impacto junto das populações. Contudo, as organizações enfrentaram problemas internos, relacionados com a ausência de recursos financeiros, com a capacitação dos seus membros e com problemas de transparência e rotatividade. O sistema de ensino desenvolve poucas competências de cidadania activa e o Estado desconfia de iniciativas de consciencialização das populações em direitos fundamentais ou em mecanismos de participação cívica. A manutenção de uma cultura política de súbdito foi funcional à penetração do grande capital na exploração de recursos naturais. As OSC enfrentam obstáculos à participação, relacionados com a forte politização da sociedade, com a desconfiança governamental em relação ao escrutínio público, proibição de manifestações públicas e receio das suas lideranças, particularmente após o início do conflito armado. A proliferação de conflitos nas áreas da indústria extractiva e a inexistência de canais formais de participação e de acesso à justiça foram agudizaram tensões, habilmente capitalizadas por grupos violentos. A guerra dispersou os membros de OSC que timidamente floresciam nos vários distritos, retirando-lhes capacidade organizativa, de advocacia e pressão social. A chegada de organizações humanitárias internacionais em resposta à emergência pouco incluiu as associações locais, reproduzindo relações assistencialistas e de dependência. O texto demonstra a urgência de identificação de líderes locais, (re)capacitação das OSC e criação de fóruns de participação social, invertendo a crença de que a violência constitui a forma possível e legítima de participação.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - portuguese / português; authority / autoridade; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; governance / governação

Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observatório do Meio Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Descolonizar os estudos urbanos em África. Conflitos armados e sustentabilidade urbana em Cabo Delgado. - Amaral, Silvia (Desafios para Moçambique 2022, 2022)
Este projecto de investigação pretende, assim, humildemente, contribuir para a descolonização dos estudos urbanos em Moçambique e Portugal, e para a transmutação dos traumas da guerra em oportunidades de desenvolvimento sustentável e prosperidade urbana.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; conflict / conflito; politics / política

Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Agrarian Change in Northern Mozambique: A ‘New’ Dimension of Research in Light of the Conflict and Violence in Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Transformação Agrária No Norte De Moçambique: Uma “Nova” Dimensão De Pesquisa À Luz Do Conflito E Violência Em Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Stemming the Insurrection in Mozambique’s Cabo Delgado (International Crisis Group, 2021)
Principal Findings What’s new? Militant attacks and security force operations in Mozambique’s Cabo Delgado province have claimed nearly 3,000 lives, while displacing hundreds of thousands of people. Insecurity has prompted the suspension of a massive gas project. The Islamic State (ISIS) claims ties to the insurrection. Southern African governments are lobbying to send troops. Why did it happen? Mozambican militants have been motivated by grievances against a state that they see as delivering little for them, despite the development of major mineral and hydrocarbon deposits. Tanzanians and other foreigners have joined up, fuelling the insurrection. The country’s historically weak security forces have been unable to stem the onslaught. Why does it matter? Unaddressed, the insurrection could spread further, threatening national stability just as Mozambique is fulfilling a peace deal with the country’s main opposition group and heading into national elections in 2024. It could worsen instability along East Africa’s coast and present ISIS with a new front to exploit. What should be done? Maputo should accept targeted assistance for security operations to contain the insurrection, and avoid a heavy external deployment that could lead to a quagmire. Authorities should deploy aid to build trust with locals and open dialogue with militants. Regional governments should redouble law enforcement efforts to block transnational jihadist involvement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conter a Insurreição em Cabo Delgado, Moçambique - International Crisis Group (International Crisis Group, 2021)
O que há de novo? Os ataques de militantes e as operações das forças de segurança na província moçambicana de Cabo Delgado já custaram praticamente 3000 vidas e deslocaram centenas de milhares de pessoas. A insegurança levou à suspensão de um gigantesco projeto de gás. O Estado Islâmico (ISIS) reivindica laços com a insurreição. Os governos do Sul de Africa estão a exercer pressão para o envio de tropas. Porque aconteceu? Os militantes moçambicanos foram motivados pelo descontentamento em relação a um estado que, do seu ponto de vista, pouco fez por eles, apesar do desenvolvimento de depósitos minerais e de hidrocarbonetos significativos. Tanzanianos e outros estrangeiros juntaram-se, alimentando a insurreição. As forças de segurança, historicamente fracas, foram incapazes de conter a ofensiva. Porque importa? Se não for tratada, a insurreição pode vir a alastrar-se, ameaçando a estabilidade nacional enquanto Moçambique está a alcançar um acordo de paz com o principal grupo de oposição do país e antes das eleições nacionais de 2024. A instabilidade ao longo da costa de Africa Oriental poderia piorar e fornecer ao ISIS uma nova frente a explorar. O que deve ser feito? Maputo deveria aceitar uma assistência direcionada para suas operações de segurança, a fim de conter a insurreição, e evitar uma mobilização externa forte, que poderia levar a uma estagnação. As autoridades deveriam fornecer assistência para construir uma relação de confiança com os habitantes locais e um diálogo aberto com os militantes. Os governos regionais deveriam redobrar seus esforços em matéria de aplicação da lei para impedir a implicação jihadista transnacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; innovation / inovação

Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Observatory of Illicit Economies in Eastern and Southern Africa (Global Initiative Against Transnational and Organized Crime, 2021)
Illicit flows are a major part of the political and economic landscape of northern Mozambique. In South Africa, the trade in poached abalone and the trafficking of synthetic drug still remain joined today. The impact that heroin capsules have had in Durban in terms of violence, profitability and local demand for heroin. How illicit gold from South Sudan and the Democratic Republic of Congo flows through Uganda
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; conflict / conflito

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Total Suspends Mozambique LNG Temporarily on Security Threat - Francois De Beaupuy; Paul Burkhardt; Borges Nhamirre (Bloomberg.com, 2021)
French energy giant Total SE suspended its $20 billion liquefied natural gas project in Mozambique indefinitely due to an escalation of violence in the area, including a March attack by Islamic State-linked militants.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Financiamento da ADIN vai agravar a já insustentável dívida pública - Beula, Emídio (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Cenário Fiscal de Médio Prazo (CFMP 2022-2024), instrumento que marca o início do ciclo de planificação e orçamentação, avança cenários preocupantes em relação à evolução da dívida pública de Moçambique. Por exemplo, as projecções relativas às despesas públicas mostram que os encargos com a dívida pública, isto é, os pagamentos de juros relacionados com o serviço da dívida, passarão de 27.114,8 milhões de meticais em 2021 para 38.731,8 milhões de meticais em 2022, evidenciando um crescimento de cerca de 42,8%. Aliás, dados apresentados pelo CFMP indicam que a tendência deverá continuar crescente, pelo menos nos próximos três (3) anos, atingindo 44.734,2 milhões de meticais em 2024, o equivalente a uma subida de cerca de 65% em relação a 2021. Apesar dessas projecções, o Governo está a mobilizar um bilião de dólares para financiar as actividades da Agência de Desenvolvimento Integrado do Norte (ADIN) nas províncias de Cabo Delgado, Nampula e Niassa. O anúncio foi feito na semana passada pelo Ministro da Agricultura e Desenvolvimento Rural, Celso Correia, o governante responsável pela tutela administrativa da instituição. A mobilização do financiamento é feita antes mesmo da aprovação do plano estratégico da ADIN, denominado Estratégia Resiliente do Desenvolvimento Integrado do Norte. O documento ainda está em consulta pública nas três províncias onde serão implementados os projectos da agência de desenvolvimento da região norte.
Keywords: ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português

Cabo Ligado 45 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Ligado 44 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Cabo Ligado 43 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Cabo Ligado 42 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado 41 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150.2020.1860026
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

State Department Terrorist Designations of ISIS Affiliates and Leaders in the Democratic Republic of the Congo and Mozambique (United States Department of State, 2021)
The Department of State has designated the Islamic State of Iraq and Syria – Democratic Republic of the Congo (ISIS-DRC) and the Islamic State of Iraq and Syria – Mozambique (ISIS-Mozambique) as Foreign Terrorist Organizations under section 219 of the Immigration and Nationality Act, as amended. The Department has also designated ISIS-DRC and ISIS-Mozambique as […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

US hits IS groups in Mozambique, Congo with terror sanctions (AP NEWS, 2021)
WASHINGTON (AP) — The Biden administration on Wednesday designated two Islamic State affiliates in Mozambique and the Democratic Republic of Congo as “foreign terrorist organizations,” imposing...
Section: World News
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

A Insurgência Jihadi em Moçambique: Origens, Natureza e Início - Morier-Genoud, Eric (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Resultante de uma investigação com trabalho de campo em Cabo Delgado em 2018 e 2019, este novo Cadernos IESE nº 21, da autoria de Eric Morier-Genoud, explica a origem, natureza, e dinâmica da guerra no norte de Moçambique com base numa análise da historicidade e das dinâmicas internas das sociedades locais. Defende o argumento segundo o qual é mais produtivo pensar nos insurgentes do Al-Shabaab em termos da sua trajectória histórica, evoluindo de uma seita islâmista para um grupo armado jihadi violento, passando actualmente por um processo de internacionalização que poderá se evoluir de várias formas no futuro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

O que vi foi a morte: crimes de guerra no "cabo esqueçido" de Moçambique (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

What I saw is death: War crimes in Mozambique's forgotten cape (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Waves and legacies: The making of an investment frontier in Niassa, Mozambique - García, Angela Kronenburg; Meyfroidt, Patrick; Abeygunawardane, Dilini; Sitoe, Almeida (AfricArXiv, 2021)
To understand how land-use frontiers emerge, we studied the actors driving investments in Niassa province, Mozambique. Our ethnographic research over 2017-2018 among commercial agriculture and forestry investors shows that successive waves of actors with different backgrounds, motives and business practices, arrived in Niassa to establish farms or plantations yet repeatedly failed. Waves come and go but leave sediments – legacies – that add up to gradually build the conditions for a frontier to emerge. The accumulation of these legacies has given rise to a new wave by actors from within the region, indicating that over time endogenous processes may replace externally-driven waves.
type: article
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; Northern PEA; agriculture / agricultura; private sector / setor privado

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

An Overview of the Policy and Market Landscape of Tobacco Production and Control in Mozambique - Nguenha, Nicole; Cunguara, Benedito; Bialous, Stella; Drope, Jeffrey; Lencucha, Raphael (International Journal of Environmental Research and Public Health, 2021)
Background: Tobacco growing has been considered a mainstay of Mozambique’s economy, but there is a dearth of analysis of the tobacco policy landscape in the country. Methods: Review of government and non-government documents and academic papers addressing Mozambique’s tobacco-growing history, the changes in the political economy of tobacco, and health policies addressing tobacco use and prevention of noncommunicable diseases. Results: Despite its tobacco growing and exporting history, the contribution of tobacco to the economy has been in steady decline in the past two decades, including in the areas dedicated to growing. At the same time there has been an increase in multinational control of the tobacco economy. In parallel, Mozambique’s commitment to addressing the growing burden of noncommunicable disease and accession to the Framework Convention on Tobacco Control indicate a potential for internal government tensions to balance immediate economic interests with long term health goals. Conclusions: With the decline in tobacco share of the overall economy, Mozambique may be well-positioned to explore alternative, sustainable livelihoods for farmers that grow tobacco, but it must overcome inter-sectoral barriers and advocate for a whole of government approach to address the health and economic impact of tobacco.
Number: 1 Publisher: Multidisciplinary Digital Publishing Institute
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Formalizing artisanal and small-scale mining in Mozambique: Concerns, priorities and challenges - Hilson, Gavin; Mondlane, Salvador; Hilson, Abigail; Arnall, Alex; Laing, Tim (Resources Policy, 2021)
This paper reflects critically on efforts made to formalize artisanal and small-scale mining (ASM) – low-tech, labour-intensive mineral extraction and processing – in Mozambique. Drawing on findings from interviews with policymakers, representatives from ASM associations and 200 individual miners, the paper captures the details of the country’s ASM formalization experience. Findings reveal that despite showing considerable promise at first, the drive to formalize ASM in Mozambique, which spans three decades, has lost considerable momentum. A bureaucratic licensing scheme, overlapping responsibilities at the Estatuto Orgaˆnico do Minist´erio dos Recursos Minerais e Energia (MIREME), and a shortage of information about miners have contributed to this slowdown. The themes underpinning the efforts to formalize ASM in Mozambique are not new but the case itself has its own unique nuances and storylines.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Inquérito Agrário Integrado 2020 - MADER (República de Moçambique - Ministério da Agricultura e Desenvolvimento Rural Direcção de Planificação e Políticas (DPP), 2021)
O crescimento agrícola em Moçambique é uma fonte essencial para promover o crescimento económico do País em geral e das famílias rurais em particular. O Programa do Governo para o Sector Agrário, em harmonia com a política económica do País, orienta-se para o alcance de grandes objectivos estratégicos, nomeadamente: (1) Segurança Alimentar; (2) Aumento do Rendimento Familiar; (3) Criação de Emprego/Inclusão Social e (4) Aumento da Produção e Produtividade. Este documento ilustra, de forma simples e clara, a situação e a dinâmica da agricultura em Moçambique durante o ano de 2020. O Inquérito Agrário Integrado (IAI 2020), indica que existem no país cerca de 4.3 milhões de explorações agro-pecuárias, das quais 4.167.702 (97.8%) são pequenas, 93.183 (2%) são médias, e 873 (<1%) são grandes explorações. Do total de cerca de 4.3 milhões de explorações (Pequenas e Médias), cerca de 6.9% receberam informação ou conselho técnico de extensão, 39.9% tiveram acesso à informação sobre preços e 0.6% acesso à crédito. A área cultivada foi de cerca de 5.5 milhões de hectares, onde 5.5% das explorações utilizaram pesticidas nos seus campos, 8.8% usaram estrume, 7.8% utilizaram fertilizantes químicos e 9.1% usou a rega. As principais culturas em diversas explorações são o Milho, Arroz, Mapira, Amendoim Pequeno, Feijão Nhemba, Feijão Boer, Mandioca, Algodão e Canade-açúcar. Grande parte das explorações cultivam Milho (83.8%), 23.6% Amendoim Pequeno, 18.3% Mapira, 12 .8% Arroz e 3.8% Mexoeira. O IAI 2020, realizado pela primeira vez com referencial distrital, é um Marco Estatístico e principal fonte de dados do sector agro-pecuário, assim como marco amostral, pois fornece dados fiáveis desagregados até ao nível Distrital, para apoiar o processo de planificação e tomada de decisão a todos níveis, baseadas em evidências científicas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura; demographics / demografia

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Humanitarian Response Plan Mozambique (United Nations Office for the Coordination of Humanitarian Affairs (OCHA), 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

The Secret to the Northern Mozambique Insurgency’s Success - Emilia Columbo (War on the Rocks, 2020)
This has been a banner year for Ahlu-Sunnah Wa-Jama (ASWJ) — or al-Shabaab, as locals call it — operating in northern Mozambique. Between January and
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

First confirmed occurrence of the yellow fever virus and dengue virus vector Aedes (Stegomyia) luteocephalus (Newstead, 1907) in Mozambique - Abílio, Ana Paula; Kampango, Ayubo; Armando, Eliseu J.; Gudo, Eduardo S.; das Neves, Luís C. B.; Parreira, Ricardo; Sidat, Mohsin; Fafetine, José M.; de Almeida, António Paulo G. (Parasites & Vectors, 2020)
Mozambique, same as many other tropical countries, is at high risk of arthropod-borne virus (arbovirus) diseases and recently two dengue virus (DENV) outbreaks occurred in the northern part of the country. The occurrence of some important vector species, such as Aedes (Stegomyia) aegypti (Linnaeus) and Ae. (Stg.) albopictus (Skuse), besides several other sylvatic vectors, have been reported in the country, which may indicate that the transmission of some arboviruses of public health importance may involve multiple-vector systems. Therefore, knowing the occurrence and distribution of existing and the new important vectors species, is crucial for devising systematic transmission surveillance and vector control approaches. The aim of this study was to map the occurrence and distribution of mosquito species with potential for transmitting arboviruses of human and veterinary relevance in Niassa Province, Northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lago; GP - Niassa; L - english / inglês; health / saúde

Indonesia's Guaranteed Microfinance Programme (KUR): Lessons from the First Stage of Implementation - ProQuest (2020)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Section: Interviews
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Mediating bureaucrats: embedded economic action in the Mozambican sugar industry - Buur, Lars; Nystrand, Malin J. (The Journal of Modern African Studies, 2020)
This article develops the concept of ‘mediating bureaucrats’ by exploring their role during liberal reforms that led to rehabilitation of the sugar industry in Mozambique. By focusing on how relations between the state, government and business are mediated by a group of cadres who have occupied positions in different social domains, the article argues that these ‘mediating bureaucrats’ cannot easily be identified in one-dimensional terms as belonging to either the public or private sector, the state or the market. It is argued that as ‘socially embedded actors’, the group of ‘mediating bureaucrats’ are in a position to translate and mediate between diverse and sometimes conflicting interests and aspirations of the state, the government and business. We use the rehabilitation of the sugar industry in Mozambique to show how mediating bureaucrats adopted two practices – muddling through and translation – in order to straddle conflicting interests during different reform initiatives in post-independence Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Insurgência: No lançamento da ADIN Nyusi ameaça reagir em caso de atentado a coesão - Anacleto, Delfim (Deutsche Welle (DW), 2020)
O norte de Moçambique passa a partir de hoje a contar com uma Agência de Desenvolvimento integrado para promover o crescimento económico e social. E em Pemba, Filipe Nyusi falou com o bispo de Pemba sobre a insurgência.
Keywords: *indexed; ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Total signs agreement with the Government of Mozambique regarding the security of Mozambique LNG project (Total.com, 2020)
Map Mozambique
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; private sector / setor privado

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Depois da ADIN, Celso Correia “ganha” Agência do Zambeze e passa a controlar o desenvolvimento do centro e norte de Moçambique - Nuvunga, Adriano (Centro para a Democracia e Desenvolvimento (CDD), 2020)
Tal como procedeu no caso da passagem da tutela da ADIN para Celso Correia, o CDD defende que a Agência do Zambeze deve estar sob tutela do Conselho de Ministros e a sua direcção deve prestar contras ao Primeiro-Ministro. À semelhança da ADIN, a Agência do Zambeze tem uma visão holística de desenvolvimento e uma actuação transversal que abrange todos os sectores económicos e sociais do Governo, pelo que não faz sentido a sua direcção responder a um Ministro responsável por um único sector, seja ele de Economia ou de Desenvolvimento. Pela sua importância estratégica para o desenvolvimento do pontecial do Vale do Zambeze, a Agência do Zambeze deve ser dirigida por gestores de reconhecido mérito recrutados através por um concurso público transparente e independente, como forma de evitar a gestão danosa e as infracções financeiras denunciadas pelo Tribunal Administrativo em 2018. Quando o Governo de Armando Guebuza criou a Agência do Zambeze em 2010, o objectivo principal era de “assegurar a eficácia e a eficiência no desenvolvimento da parte nacional da bacia hidrográfica do Vale do Rio Zambeze, uma das regiões cujo potencial de recursos e as possibilidades de aproveitamento estudadas apontam como susceptível de, rapidamente, contribuir para o desenvolvimento e crescimento económico e humano auto-sustentado do país”. Volvidos 10 anos depois, a Agência do Zambeze ainda não deu sinais de estar a explorar as potencialidades do Vale do Zambeze para dinamizar o desenvolvimento das províncias do centro do país, que concentram boa parte da população pobre de Moçambique. O Vale do Zambeze tem potencial energético, grandes depósitos de minerais como carvão e ferro, para não falar do potencial agro-pecuário subaproveitado. Não foi por acaso que o político português Almeida Santos uma vez declarou: “Quem tem o Vale do Zambeze não pode ser um país pobre”6. Mas os cerca de 12 milhões de pessoas que vivem nas quatro províncias atravessadas pelo Vale do Zambeze continuam num vale de pobreza.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; rural development / desenvolvimento rural

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Publisher: Routledge _eprint: https://doi.org/10.1080/13600826.2020.1772730
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

How Do Donor-led Empowerment and Accountability Activities Take Scale into Account? Evidence from DFID Programmes in Contexts of Fragility, Conflict and Violence - Anderson, Colin; Fox, Jonathan; Gaventa, John (2020)
Development donors invest significantly in governance reform, including in contexts characterised by conflict and fragility. However, there is relatively little comparative study of their change strategies, and little understanding of what works and why. This paper explores the strategies of six recent DFID-funded programmes in Mozambique, Myanmar, and Pakistan with empowerment and accountability aims. Document review and field interviews are used to analyse the application of multi-scalar or multi-level change strategies, since such approaches are hypothesised to potentially generate more leverage for public accountability reforms. Analysis suggests that these strategies can strengthen citizen ability to navigate governance systems to resolve problems and claim accountability, and can bolster pro-accountability coalitions’ internal solidarity and external legitimacy. Multi-level strategies also appear associated with establishing more significant pressure for reform than exclusively local or national approaches. Yet conventional project reporting focuses on counting activities and outputs rather than analysing the dynamic, interactive processes at work in these strategies, and few evaluations are publicly accessible. To fully understand what kinds of action strengthen citizen demands for accountability requires a more transparent and rigorous approach to learning from donor-led governance interventions.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Desenvolvimento socioeconómico de Cabo Delgado num contexto de conflito - João Feijó; António Souto; Jerry Maquenzi (Observador Rural, 2020)
Um conjunto de contradições internas e de longa duração estruturam as relações socioeconómicas na província, estando em grande medida na origem da conflitualidade actual. Não obstante a crescente interferência de factores externos na dinamização do conflito, os dados disponíveis permitem-nos concluir que, enquanto persistirem elementos internos de contradição, não será possível encontrar uma solução sustentável para o conflito. Não obstante o conflito implicar, inevitavelmente, uma intervenção militar, para prover a segurança das populações e de bens, as profundas contradições internas existentes obrigam à realização de um plano de desenvolvimento social e económico, entendido como a melhor estratégia de contra-insurgência, limitando o alastramento do conflito armado por outras zonas da província marcadas pela pobreza e por históricas relações de protesto em relação ao Estado. Uma vez que as informações são escassas e imprecisas e a situação militar no terreno é bastante imprevisível, torna-se difícil definir linhas gerais para um plano de intervenção. Não obstante, neste documento pretende-se apresentar um conjunto de elementos que devem ser considerados, de forma coerente, na implementação de qualquer projecto de desenvolvimento, distinguindo as diferentes áreas socioeconómicas de intervenção na província de Cabo Delgado, em função da realidade actual.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict / conflito; economic development / desenvolvimento económico

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Spatio-temporal patterns of wildfires in the Niassa Reserve –Mozambique, using remote sensing data - Nhongo, Eufrásio; Fontana, Denise; Guasselli, Laurindo (2020)
Wildfires are among the biggest factors of ecosystem change. Knowledge of fire regime (fire frequency, severity, intensity, seasonality, and distribution pattern) is an important factor in wildfire management. This paper aims to analyze the spatiotemporal patterns of fires and burned areas in the Niassa Reserve between 2002-2015 using MODIS data, active fire product (MCD14ML) and burned area product (MCD64A1). For this, the annual and monthly frequencies, the trend of fires and the frequency by types of forest cover were statistically analyzed. For the analysis of the spatial dynamics of forest fires we used the Kernel density (Fixed Method). The results show a total of 20.449 forest fires and 171.067 km2 of burned areas in the period 2002-2015. Fire incidents were highest in 2015, while the largest burned areas were recorded in 2007. The relationship between increased fires and burned areas is not linear. There was a tendency for fires to increase, while for burnt areas there was stabilization. Forest fires start in May and end in December. August-October are the most frequent period, peaking in September. Fires occur predominantly in deciduous forests and mountain forests because of the type of vegetation and the amount of dry biomass. There is a monthly spatial dynamics of wildfires from east to west in the reserve. This behavior is dependent on vegetation cover type, fuel availability, and senescence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; natural disasters / desastres naturais

The implementation of ASEAN single window in Indonesia as an effort to facilitate the flow of import and export in Indonesia - Arifin, Jamilah (2020)
On 9 December 2005, All ASEAN member countries signed the Agreement to Establish and Implement the ASEAN Single Window. ASEAN Single Window (ASW) is a one window system that connects ASEAN countries or National Single Window (NSW) to facilitate the electronic exchange of customs data that can be used by traders to obtain permits, customs clearance, and other documents. Indonesia has been implementing this Agreement from 2008 with the system of Indonesia National Single Window (INSW) in order to improve the smooth flow of goods and the performance of export-import services. By using the normative legal research, the research aims to determine the implementation of the ASEAN Single Window (ASW) system as an effort to facilitate the flow of exports and imports in Indonesia. The research shows that the implementation of ASEAN Single Window in Indonesia through Indonesia National Single Window System has helped improve efficiency and import export activities through its service contribution.
Keywords: *indexed; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Economic brief - The Africa Infrastructure Development Index (AIDI) 2020 - African Development Bank (African Development Bank, 2020)
The development of infrastructure in Africa is critical for fostering economic growth and improving the living standards of Africans. It contributes significantly to human development, poverty reduction, and the attainment of the Sustainable Development Goals (SDGs). Investment in infrastructure accounts for over half of the improvements in economic growth in Africa witnessed over the last decade and has the potential to contribute much more, given a conducive environment.
Publisher: African Development Bank Group
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

BTI 2020 Mozambique Country Report - BTI (2020)
“Mozambique faces five major challenges: violence between political camps, impunity with regard to corruption, violations of human rights, the debt crisis and the security threat of Islamist terrorism.”
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

Ugandenses e Tanzanianos do Al-Shabaab: um olhar à dimensão internacional do conflito em Cabo Delgado - Chichava, Sergio (Desafios para Moçambique, 2020)
O conflito militar que, desde 5 de Outubro de 2017, se abate sobre Moçambique, com particular incidência na província de Cabo Delgado e protagonizado por um grupo localmente conhecido por Al-Shabaab, cuja pretensão é substituir o Estado laico por um Estado regido pela Sharia, tem sido regularmente descrito pelas autoridades moçambicanas como tendo, além de uma dimensão interna, uma componente externa. Desde o início do conflito, as autoridades locais falam da prisão ou da procura de vários estrangeiros que estariam a treinar, financiar e dirigir a «insurgência» em Cabo Delgado com vista a retardar o desenvolvimento do País e a explorar ilegalmente diversos recursos naturais. De entre os diversos estrangeiros frequentemente mencionados, o destaque vai para tanzanianos e ugandenses. Por seu turno, o Al-Shabaab tem vindo a reclamar uma dimensão internacional, declarando fidelidade ao Estado Islâmico (EI) ou Daesh. Ao que tudo indica, o Daesh também reconhece o Al-Shabaab, que designa por «soldados do Califado» pertencentes ao Estado Islâmico da Província da África Central (ISCAP, no acrónimo inglês), uma região cujos contornos geográficos ainda não estão bem claros, mas que englobaria actualmente, além Moçambique, a República Democrática do Congo (RDC), País onde está baseado o grupo islamista ugandês Forças Democráticas Aliadas (ADF), que também tem sido apresentado nalguns fóruns como tendo relações com o Al Shabaab em Moçambique, através da presença de alguns dos seus militantes neste País, ou através do recrutamento e treino de jovens moçambicanos na RDC. Com base nos elementos acima, o objectivo deste texto é fazer uma breve análise da componente internacional do AlShabaab, olhando para a sua ligação com a Tanzânia, o Uganda e o EI. Mais precisamente, olhando para o perfil dos cidadãos ugandeses e tanzanianos que têm sido referenciados como sendo do Al-Shabaab, o texto procura responder às seguintes questões: quem são os tanzanianos e ugandeses do Al-Shabaab? Como chegaram a Moçambique? O que pretendem? Porque escolheram a província de Cabo Delgado? Será o Al-Shabaab uma filial do Estado Islâmico? Para responder a estas questões, primeiro apresenta-se o perfil dos tanzanianos e ugandeses do Al-Shabaab; a seguir, apresentam-se algumas hipóteses sobre as suas pretensões; e, por último, abordam-se alguns elementos sobre a possível ligação do Al-Shabaab ao Daesh ou ao EI.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
978-84-09-17639-7
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Introdução - Forquilha, Salvador (Desafios para Moçambique 2020, 2020)
Trinta anos depois da aprovação da primeira Constituição multipartidária da história do País,2 Moçambique continua a enfrentar grandes desafios no processo da construção democrática. Com efeito, não só as instituições que resultaram das reformas políticas no âmbito da nova Constituição têm demonstrado fragilidades no seu funcionamento, como também as regras do jogo político têm sido marcadas por uma certa instabilidade, consubstanciada, por exemplo, nas sucessivas revisões da legislação eleitoral. Nos últimos índices de democracia,3 Moçambique tem registado recuos significativos na sua pontuação. Depois de ter passado de regime híbrido para regime autoritário (The Economist, 2019), o País passou da posição 116, em 2018, para a posição 120, em 2019 (The Economist, 2020). No que se refere à situação económica, a trajectoria do País tem sido marcada por crises e contradições, resultantes, essencialmente, das estruturas sociais de produção, das dinâmicas de dependência e do sistema social de acumulação (Castel-Branco, C.N., 2020a). No plano social, apesar de ter havido uma ligeira melhoria em termos de bem-estar e uma redução percentual da taxa de pobreza de consumo em 5 % entre 2008/2009 e 2014/2015, de acordo com os dados do Inquérito aos Orçamentos Familiares (IOF) 2014/2015, análises indicam que ainda persistem diferenças significativas regionais e entre os espaços urbano e rural ao longo do País. Com efeito, «a redução da pobreza no período entre 1996/1997 e 2014/2015 foi substancial tanto nas áreas rurais como urbanas, mas a redução foi mais acentuada nas áreas urbanas entre 2008/2009 e 2014/2015. A nível regional, evidencia-se que o Norte piorou a própria situação em termos de taxa de pobreza de consumo, passando de 45 % para 55 %, enquanto o decréscimo das taxas de pobreza no Centro e no Sul foi, respectivamente, de 10 e 18 pontos percentuais. Entre 2008/2009 e 2014/2015, a pobreza diminuiu em todas as províncias do Centro e Sul, particularmente em Maputo (província e cidade), enquanto nas três províncias do Norte as taxas de pobreza estagnaram ou cresceram» (Arndt et al., 2018: 311). Os dados acima também indicam que a pobreza é muito resiliente em relação ao crescimento económico – no mesmo período em que baixou 5 % (a uma média anual de -0,8 %) o PIB cresceu 50 % (a uma média anual de 7 %), revelando que o padrão de crescimento económico é pouco eficiente a reduzir pobreza.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; poverty / pobreza

Face ao conflito no norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgago - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2020, 2020)
A história de Moçambique dos últimos 50 anos tem sido marcada por ciclos de violência armada de contestação ao Estado, não só colonial, como também pós-colonial. Com efeito, desde a guerra anticolonial levada a cabo pela Frente de Libertação de Moçambique (Frelimo), passando pela guerra civil, que opôs a Resistência Nacional Moçambicana (Renamo) ao Governo da Frelimo, até às crises político-militares pós-eleitorais, a violência armada tem estado presente no processo da construção do Estado em Moçambique. No início de Outubro de 2017, começou uma outra contestação violenta ao Estado na província de Cabo Delgado. No dia 5 de Outubro de 2017, um grupo de homens armados atacou as instituições do Estado na vila sede de Mocímboa da Praia. Inicialmente associado a um banditismo de mera perturbação da ordem pública, o fenómeno ganhou rapidamente proporções alarmantes. Os ataques começaram a multiplicar-se. Dois meses depois do primeiro ataque, a Polícia já havia detido 251 suspeitos, dos quais 37 eram cidadãos de nacionalidade tanzaniana (O País, 2017). Em Dezembro de 2017, a Polícia da República de Moçambique, ao mais alto nível, esteve na zona e visitou os distritos de Mocímboa da Praia e Palma. No comício popular que realizou na vila sede de Mocímboa da Praia, o Comandante Geral da Polícia, Bernardino Rafael, deu um «ultimato» aos atacantes de Mocímboa da Praia, decretando sete dias para se entregarem às autoridades (O País, 2017). No entanto, a violência continuou e, nas semanas e meses que se seguiram ao ataque à vila sede de Mocímboa da Praia, a situação de segurança piorou no terreno e os ataques espalharam-se para outros distritos da zona norte de Cabo Delgado. Entre finais de Março e meados de Abril de 2020, a violência armada atingiu níveis nunca vistos antes, com o assalto e a ocupação temporária de quatro vilas nos distritos de Mocímboa da Praia, Quissanga, Muidumbe e Ibo. Que factores estão na origem do avanço da insurgência no terreno? Que tipo de relação se vai desenvolvendo entre os insurgentes e as populações locais? Existe algum potencial para que a insurgência se alastre para o Sul, em direcção à zona costeira de Nampula? Como tem vindo o Estado a responder à insurgência? Estas perguntas são uma parte importante do programa de pesquisa intitulado «Estado, violência e desafios de desenvolvimento no Norte de Moçambique», em curso no IESE desde Agosto de 2019.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Decentralization reforms in Mozambique: The role of institutions in the definition of results - Forquilha, Salvador; UNU-WIDER (UNU-WIDER, 2020)
Abstract: With the introduction of the economic reforms in the late 1980s, the opening up of the political arena and the end of the civil war in the early 1990s, the decentralization process began in Mozambique. Different research developed in recent years shows that, as is the case in other countries in sub-Saharan Africa, the impact of the decentralization reforms on the promotion of local development and the strengthening of democracy in Mozambique is modest. How can this modest impact be explained? Based on three important reforms in the decentralization process in Mozambique, namely the ‘7 million’, municipalization and decentralized provincial governance, this article seeks to answer this question by analysing how different aspects of the institutions affect the results of the reforms. The main argument in the article underlines the idea according to which the results of the decentralization reforms in Mozambique are constrained by the nature and by the operation mechanisms of the political system. Of these institutional factors/constraints, state capacity and independence from private interests, particularly political groups, stand out in the three reforms analysed throughout this article. In this context, the reforms develop according to group interests, particularly party political interests, which capture the state and use the reforms as a mechanism for maintaining and bolstering political power. In this sense, rather than being a means of improving the provision of public services and strengthening democracy, decentralization works more as an instrument for reinforcing state control and pandering to the elite. This is probably the biggest challenge decentralization is facing in Mozambique, therefore making it a fundamental issue to be taken into account in any reform in this area, within the context of strengthening democracy and promoting local development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Campanha Agrícola 20/21: Mais de 300 mil hectares lavrados na campanha agrícola 2020/21 - MADER (Agricultura, 2020)
Mais de 300 mil hectares lavrados na campanha agrícola 2020/21
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água; higiene e saneamento; health / saúde

Cabo Delgado e o Risco Sistémico da Guerra em Moçambique - Ngoenha, Severino; do Amaral, Giverage; Nhumaio, Alcido (Desafios para Moçambique 2020, 2020)
Em Moçambique a guerra é um risco sistémico: na linguagem de Thomas Hobbes, é a mãe de todos os riscos. A guerra é transversal a todos os outros riscos em termos de consequências sociais, económicas, políticas e culturais: destrói as infra-estruturas, como a rede escolar, os hospitais, as vias de acesso e os tecidos sociais; enfraquece a economia; paralisa a agricultura; apodera-se da indústria; e instala a fome, a miséria e toda a espécie de desgraças. A guerra é o maior dos riscos sistémicos de Moçambique não apenas pelos seus efeitos altamente destrutivos, mas porque agrava a probabilidade de ocorrência dos demais riscos aos quais o País está sistemática e concomitantemente exposto. Em geral, as considerações sobre a guerra em Moçambique são feitas de duas maneiras diferentes. De um lado, a abordagem político-militar, que privilegia a busca de mecanismos de diálogo entre os beligerantes, o que supõe o conhecimento e o reconhecimento entre as partes e das razões que levam uns e outros a optar por um confronto armado. Esta abordagem tem sido a adoptada pelos diferentes governos moçambicanos que enfrentaram conflitos nos seus mandatos, ou seja, todos. Actualmente não parece que uma tal via se vislumbre salutar nas estratégias contra os dois conflitos armados em curso no Centro e Norte do País. Por outo lado, a abordagem técnico-científica, que parte do pressuposto de que o fenómeno da guerra é complexo e privilegia uma epistemologia interdisciplinar, na qual participam muitos saberes disciplinares no esforço de apreender as suas razões e causas. Esta abordagem procura entender o que leva o País a fazer da guerra o seu modus vivendi, o que leva grupos, partidos e facções militares a optarem sistematicamente pela confrontação militar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

O Cabo do Medo - O Daesh em Moçambique 2019-2020 - Rogeiro, Nuno (UCCLA, 2020)
Toda a verdade sobre a situação explosiva do domínio do Norte de Moçambique pelo Daesh. É o primeiro livro a nível mundial que revela em primeira mão o que se está a passar na zona de Cabo Delgado: a conquista e subjugação das populações, a violência bárbara com recurso a decapitações e execuções sumárias, a exploração das pessoas e dos recursos disponíveis, a impotência das autoridades moçambicanas em impor a ordem e a paz social. Um livro de grande acualidade que desvenda uma realidade tão chocante quanto desconhecida. “Uma análise exaustiva da ocupação desta terra boa (nordeste de Moçambique), de gente boa, pelo Daesh. Tem de ser combatido mas, primeiro, tem de ser compreendido.” Nuno Rogeiro
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Investimento Directo Estrangeiro e o Desenvolvimento Socioeconómico em Moçambique: Dinâmicas, Tensões e Desafios - Sambo, Michael Godet (Desafios para Moçambique 2020, 2020)
Considerando a estrutura económica de Moçambique e analisando a estrutura do IDE que aflui a Moçambique, este artigo argumenta que o aumento de IDE na economia não é necessariamente a condição para o desenvolvimento se não for maximizada a captação e utilização das receitas. Embora a lógica de fomento do desenvolvimento económico através do investimento adoptada pelo Governo de Moçambique no PQG 2015-2019 tenha um embasamento teórico, o seu enquadramento é simplista e pouco considera a natureza do investimento, o contexto em que este é aplicado e o seu efeito estrutural na economia. O argumento resulta, além da revisão bibliográfica e documental, de uma análise dos dados económicos oficiais de Moçambique, com destaque para os dados do IDE publicados pelo Banco de Moçambique, conjugados com a análise dos materiais de trabalhos de campo sobre o IDE na província de Nampula em 2016 e na Província de Gaza em 2019. O texto está estruturado em três partes além da introdução e conclusão. A primeira faz um enquadramento teórico da discussão, a segunda analisa as dinâmicas de IDE na economia e a terceira analisa algumas evidências empíricas dos efeitos socioeconómicos causados pelos projectos de IDE nas comunidades receptoras dos projectos.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
OCLC: 1164631287
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito